IMPORTANCE OF CAROTENOIDS FOR HUMAN HEALTH - Semih ÖTLEŞ; Yeşim ATLI (Pamukkale University Journal of Engineering Sciences, 1997)
Carotenoids are brightly yellow to red pigments occuring in plants and are introduced into humans through dietary intake of vegetables and fruits. They do not dissolve in water, they can give maximum absorption in UV region at 400-450 nm., and they are stable in alkali. Some carotenoids have provitamin A activity and they are important because of the synthesis of Vitamin A needed to be taken into the body. In addition to this function, carotenoids play very important roles in preventing diseases caused by Vitamin A deficiency, coronary heart diseases, and cancer. They are effective in preventing or at least slowering cancer as a result of their antioxidative properties. Studies are shown that cancer risk (especially the lung cancer) decreases with the intake of carotenoids. As a conclusion vegetables and fruits-rich diet is always important and valuable for healty populations.